The Effects of Internal Attention on Knee Biomechanics in Volleyball Spike Jump through Augmented Video Feedback - Aiwen Wang; Xiaohan Li; Huiming Huang (Brain Sciences, 2021)
Poor knee biomechanics in a volleyball spike jump generally result in a higher knee injury risk, which can be altered by an internal focus of attention (FOA). The constrained action hypothesis (CAH) purports that the FOA inhibits sports performance whereas no ecologically valid evidence has been found in previous studies. The purpose of this research is to explore the effect of video feedback on knee biomechanics in a volleyball spike jump including landing and take-off phases. The video feedback was performed in a natural way. Fourteen volleyball male players were recruited in this study. A paired t-test was used to detect the effect of the feedback; meanwhile, statistical parameter mapping (SPM) statistics were used for the continuum differences during movement. After biofeedback, the initial contact flexion angle of the knee (t = 2.179, p = 0.049), the maximal flexion angle of the knee (t = 3.242, p = 0.006) and the maximal internal rotation angular velocity of the knee (t = 5.209, p = 0.003) increased significantly; the maximal extension moment of the knee (t = 3.962, p < 0.001) and the maximal flexion moment of the knee (t = −3.711, p = 0.002) significantly decreased; the maximal abduction moment significantly decreased (t = 3.069, p = 0.037) but the maximal internal rotation moment significantly increased (t = 2.813, p = 0.018); the first peak of the vertical ground reaction force (vGRF) (t = 7.618, p < 0.001) and the average loading rate to the first peak (t = 4.205, p = 0.004) significantly decreased; the other peaks of the vGRF were not found to have differences; a larger knee flexion was found during the phase from 31.17 to 73.19% (t = 2.611, p = 0.012); a larger adduction angular velocity was found during the phase from 49.07 to 62.46% (t = 3.148, p = 0.004); a smaller external rotational angular velocity was found during the phase from 45.85 to 49.96% (t = 5.011 p = 0.017); there was an increased flexion moment of the knee during the phase from 19.72 to 21.38% (t = 0.029, p = 0.029) and an external moment of the knee during the phase from 85.55 to 95.06% (t = 4.214, p < 0.001); the vGRF significantly decreased during the phase from 3.13 to 5.94% (t = 4.096, p = 0.014) and 19.83–21.97% (t = 4.096, p = 0.024) but significantly increased in the phase of 91.43–100% (t = 4.096, p < 0.001). The impulse of the vGRF and knee power were not found to be different compared with before biofeedback. Therefore, our study suggests video feedback in a natural practice has the potential to improve knee movement whilst not altering the performance in a volleyball spike jump. This indicates that the CAH theory is possibly not suitable in a real competition. Due to the complexity of human movements and the limitations of this study, muscle activities must be considered in the future.